Power of the people: A review of citizen science programs for conservation. (September 2020) - MacPhail, Victoria J.; Colla, Sheila R.
Abstract: Citizen science is a rapidly growing field whereby volunteers can collect and/or analyze data to contribute to research and gain an appreciation for the environment. There are countless programs currently underway around the world: some have clear scientific hypotheses being tested and others are simple data gathering; some are designed and led at the grass-roots level while others are done by academics. This review focusses on best practices for the development and running of citizen science projects to make them successful. It includes discussion around different methods of experimental design, data collection, and analyses; how participants are recruited, engaged, and rewarded (including who participates and why); the effect of participation on the volunteer's knowledge and actions; and the impact programs have on policy and other conservation actions. While there are several challenges that projects face, and more research is needed in various areas, the many benefits support the continued expansion of citizen science projects. Highlights: Consistent definitions, protocols are needed to improve the citizen science field. Citizen science provides benefits to participants, scientists, society, environment. Challenges relate to economics, volunteer management, data analysis. Experimental design, data management, data sharing are key areas to plan carefully. Best practices for developing and running projects are discussed.